Tobacco influence on the neonatal outcome (Italian Journal of Public Health, 2010)
Background: Cigarette smoking, active or passive, is related to adverse perinatal outcomes, increased risk ofspontaneous abortions, preterm delivery, low birth weight, malformations, placenta previa, and abruption.It is also known to have adverse effects on the fetus and newborn, as well as affecting breastfeeding. Theliterature data gave the initial idea to identify some possibly smoking-influenced conditions on perinatal/neonatal outcome indicators.Patients and Methods: Newborns and their mothers admitted to Gynecology& Obstetric Clinic, Skopje,Macedonia were selected to participate in the study. The patients were divided into 3 groups: the first groupconsisted of newborns unexposed to tobacco smoke, the second group were newborns born to motherswho smoked more than 20 cigarettes per day, who did not try to quit smoking during the pregnancy, andthe third group were newborns born to the mothers who don’t smoke, but were in close contact with othersmokers (intensively exposed to the tobacco smoke).Methods used: epidemiological, clinical examinations,biochemical analysis and statistical analysis of the results.Our results clearly demonstrated that maternal smoking had a significant effect (p
Keywords: newborn; cigarette smoke; outcome; prematurity